2022
DOI: 10.1038/s41598-021-04666-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke treatment with argon preserved neurons and attenuated microglia/macrophage activation long-termly in a rat model of transient middle cerebral artery occlusion (tMCAO)

Abstract: In a previous study from our group, argon has shown to significantly attenuate brain injury, reduce brain inflammation and enhance M2 microglia/macrophage polarization until 7 days after ischemic stroke. However, the long-term effects of argon have not been reported thus far. In the present study, we analyzed the underlying neuroprotective effects and potential mechanisms of argon, up to 30 days after ischemic stroke. Argon administration with a 3 h delay after stroke onset and 1 h after reperfusion demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 58 publications
1
15
0
1
Order By: Relevance
“…Moreover, we observed a better neurological outcome in neuroprotected animals, but this observation remains qualitative due to the limited size of our experimental groups. Overall, our results confirm the neuroprotective effects of argon inhalation observed in rat models of MCAO in terms of both infarct volumes[11,12,14] and neurological dysfunction[23,24]. However, in contrast to these rodent studies, we showed that the neuroprotective effect is limited to the cortical sheet, which was mainly affected in our NHP model of tMCAO.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, we observed a better neurological outcome in neuroprotected animals, but this observation remains qualitative due to the limited size of our experimental groups. Overall, our results confirm the neuroprotective effects of argon inhalation observed in rat models of MCAO in terms of both infarct volumes[11,12,14] and neurological dysfunction[23,24]. However, in contrast to these rodent studies, we showed that the neuroprotective effect is limited to the cortical sheet, which was mainly affected in our NHP model of tMCAO.…”
Section: Discussionsupporting
confidence: 87%
“…There were 16 in vitro studies, seven ex vivo studies, and 37 in vivo studies (six of which also included in vitro experiments). 1 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 Details of these studies are presented in the Supplemental materials ( Supplemental Tables S7 and S8 ). The sex of humans, animals, cells, and tissues involved are documented in Supplemental Table S7 (under the column labelled “cell tissue”) and…”
Section: Resultsmentioning
confidence: 99%
“…3 , panel a). 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 40 , 41 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 60 , 62 , 63 , 64 , 67 , 68 , 69 , 71 , 73 , 74 , 75 , 76…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Therefore, argon draws more and more attention as a promising new treatment for stroke. It is reported that argon exposure attenuates neuroinflammation and injury whereas enhances M2 microglia/macrophage polarization in rat tMCAO model ( Liu et al., 2019 , 2022 ). However, the effect of argon on M1 microglia/macrophage and NLRP3 inflammasome has not been reported, and the mechanism underlying the neuroprotective properties of argon is not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%